ANALISIS KELAYAKAN INVESTASI PADA PT. DANAREKSA SEKURITAS DENPASAR - I Gede Sedana Arta; Ni Wayan Suartini; Ni Puru Yuli Tresna Dewi (Nusantara Hasana Journal, 2024)
This study aims to determine the performance of the financial ratios of the largest securities issuers of mutual funds and the assessment of the largest securities portfolio of mutual funds of PT Danareksa Sekuritas Denpasar using the Single Index Model. In addition, the purpose of this study was to determine the performance assessment of the largest securities portfolio of PT Danareksa Sekuritas Denpasar using the Sharpe method.The population in this study is the securities spread in the Danareksa PT. Sekuritas Denpasar Mutual Fund, namely all sectors included in the JII Index. The research sample in this company is the Largest Securities included in the DINAR propectus in April 2016. The sampling technique uses a non-probability sampling method. The results of this study are from the results of the discussion of financial ratios above it can be concluded that most of the ratios of companies included in the largest securities of Danareksa mutual funds analyzed in the past 4 years have decreased, it can happen that the company belongs to the JII and includes an optimal portfolio but has poor financial ratios, this needs further research. Because investors prefer to invest in mutual funds for more than the next 3 years and the issuers are blue chip stocks. The first portfolio is sharia stocks and must be listed on the JII. Assessment using the Single Index Model is known with higher portfolio beta results, which means the greater the beta indicates the greater the volatility faced because it fluctuates greatly in the market, so that if investing short-term in this mutual fund will be very risky, but for the long term this mutual fund will be promising because the market will experience a change in trend. The results of the evaluation of Danareksa mutual funds using the sharpe ratio that in April and May showed a declining performance, because the average rate of return of mutual funds was below the average risk-free rate of return. However, performance strengthened in June on the latest April 2023 portfolio.